Governance and ethics architecture: a study of five urban local authorities in Zimbabwe - Mutema, Edson P. (Midlands State University, 2017)
Corruption is acknowledged as one of the greatest challenges affecting urban councils in Zimbabwe. It is common to open a newspaper and discover a story highlighting the ethical violations and corrupt activities of urban council officials. The prevalence of corruption in Zimbabwe’s urban local authorities is considered in this study as the litmus test on the capacity of the existing ethics architecture to fight corruption. Ethics architecture refers to systems and structures in the form of a set of rules, institutions and practices designed by urban local authorities to promote ethical conduct against corruption. This study sought to evaluate the performance of the ethics architecture of urban councils in Zimbabwe and to propose relevant policy and institutional improvements. The study is situated within teleological, deontological and virtue ethics theories and argues that one cannot exist in isolation and should be unified to underpin the study. Analysed through the lens of a three pronged theory of ethics, the conceptual and theoretical framework provides a benchmark to conduct a comparative analysis of Norway, Singapore, Botswana and South Africa ethics architecture, including that of Zimbabwe in order to come up with ethics architectural remedies that are internationally aligned but locally relevant to stamp out corruption in Zimbabwe. Fighting corruption and its manifestation in these four countries, two international and two continental have common grounds of political will, institutional and legal enforcement practices. The qualitative methodology was employed to collect data from five sites through documentary analysis, interviews and observations, this allowed for replication of logic to occur and the production of compelling and reliable results. The five sites included Gweru City Council, Mutare City Council, Bindura Municipality, Redcliff Municipality, and Zvishavane Town Council. Data analysis in this study involved detailed case by case analysis followed by a comparative thematic and cross analysis of the five urban local authorities’ cases. The study was able to draw conclusions and to make recommendations. The study concludes that the ethics architecture for urban councils is not effective to counter the problem of corruption. The practice of good ethics and effective ethics architecture therefore, forms a sound backbone to fight corruption and all its manifestations. The study reveals that Zimbabwean urban councils should adopt effective ethics architectural remedies which are capable of fighting corruption head-on from detection, investigation and prevention to resolution point of view. The study therefore recommends that urban councils should conduct v ethics training programs for their employees and elected officials to raise ethics consciousness and to build skills capable of identifying and resolving ethical dilemmas from primary school level to adulthood as a long- term measure, and parents should participate in the integrity crusade by inculcating ethical values and moral uprightness during the formative years of their children. The study further recommends that socialisation as a preventive measure is very critical because the acts of corruption are committed under the cover of secrecy, which implies that corruption can evade detection, prosecution and sanction. Against such a background, the need for proper socialisation of the inner person cannot therefore be overemphasised for urban councils in Zimbabwe. The growth of the moral fabric of the inner person takes superiority over the legal remedy which is reactive and costly. But, on its own, socialisation is inadequate to eradicate the vice of corruption, so sanctioning and enforcement through the legal remedy plays a complementary role. The sanctioning process follows the stages of detection, investigation and resolving corruption by enforcing asset and financial declarations for both elected and senior appointed officials and enacting legislation which protects whistle-blowers against occupational detriments. Overall, effective ethics architectural remedies managed by an Integrity Management Office (IMO) is crucial in the battle against corruption and this should be supported by exemplary leadership, well-paid workforce, robust and balanced media platforms and active citizenry. The ethics architectural remedies in this study are recommended to be adopted and experimented as a liberating praxis and solution to ethical problems and challenges confronting the urban councils in particular, and Zimbabwe in general. The study identified areas that need further research. First, a similar study which infuses both quantitative and qualitative methods is needed to complement the limitations of this study. Second, research that substantiates the involvement of civil society groups and the media in raising alarm bells when ethics is violated is recommended. Third, in this study the examination of the ethics architecture is delimited to urban local authorities, so the other area of research that needs urgent attention is a comparative study between rural and urban councils’ ethics architectural remedies. This comparative study will unearth reasons why corruption is more prevalent in urban councils than in rural councils as revealed in this study.